Pengaruh Audit Tenure, Ukuran Kantor Akuntan Publik, Rotasi Audit, Dan Audit Delay Terhadap Kualitas Audit Pada Perusahan Manufaktur Subsektor Makanan Dan Minuman - Sisca Maria; Murtanto Murtanto; Hermi Hermi (Jurnal Mutiara Ilmu Akuntansi, 2023)
This research aims to find out whether audit tenure, KAP size, audit rotation, and audit delay have an effect on audit quality in manufacturing companies with the food and beverage subsector listed on the Indonesia Stock Exchange (BEI) in 2019-2022, either partially or simultaneously. The type of data in this research is quantitative with secondary data. The sample used in this research was 30 food and beverage companies with 128 financial reports. The sampling technique uses purposive sampling technique. The analytical methods used in this research are logistic regression analysis and descriptive analysis. The results of this research show that audit tenure has a positive and significant effect on audit quality, while KAP size, audit rotation and audit delay do not have a significant effect on audit quality.